2020
DOI: 10.1093/ije/dyz259
|View full text |Cite
|
Sign up to set email alerts
|

Data Resource Profile: Mental Health of Children and Young People (MHCYP) Surveys

Abstract: UK, Mental health, Children and young people, Surveys Data Resource basicsThere is an increasing international focus on mental health with a particular emphasis on its importance among children and young people (Patel at al. 2018). Large population-based datasets with robust measures therefore present an important resource for policy and practice related researchers, particularly if they incorporate longitudinal data.The Mental Health of Children and Young People Surveys (MHCYP) comprise three comparable cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…Likewise, a representative community sample in the United Kingdom reported higher levels of anxiety and trauma symptoms during the COVID-19 period as compared to previous population studies (Shevlin et al, 2020). Similar results were also found in the US, India, and many other countries (Ford et al, 2020;Holmes et al, 2020;Othman, 2020;Roy et al, 2020).…”
Section: Introductionsupporting
confidence: 83%
“…Likewise, a representative community sample in the United Kingdom reported higher levels of anxiety and trauma symptoms during the COVID-19 period as compared to previous population studies (Shevlin et al, 2020). Similar results were also found in the US, India, and many other countries (Ford et al, 2020;Holmes et al, 2020;Othman, 2020;Roy et al, 2020).…”
Section: Introductionsupporting
confidence: 83%
“…The pandemic is occurring against the backdrop of increased prevalence of mental health issues in the UK in recent years in some groups. 1,2 Furthermore, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19, might infect the brain or trigger immune responses that have additional adverse effects on brain function and mental health in patients with COVID- 19.…”
Section: Introductionmentioning
confidence: 99%
“…With a nationwide school closure, the emergency home schooling plan has been implemented and online courses were offered to children in a well-organized manner by schools and teachers. Although these measures ensured that school learning was not largely disrupted, prolonged school closure and home quarantine might have negative impacts on children's mental health (Brazendale et al 2017;Brooks et al 2020), as previous work suggested that children experienced anxiety and depression when facing flexible and rapidly changing situation (Dalton 2020;Tamsin et al 2020). Indeed, a recent study showed that children suffered greater psychological impact of the outbreak and experienced psychological crisis, which result in a variety of psychological problems such as anxiety and depression (Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%